El tratado Ars rhetorica y el comentario al Timeo de Casio Longino. Testimonios de La Recepción de Platón en La Antigüedad Tardía - Sánchez Castro, Liliana Carolina (Revista Archai, 2016)
The Ars Rhetorica of Cassius Longinus is not a work that has enjoyed particular popularity in studies of ancient rhetoric or on the philosophical activity in Late Antiquity. This is due, in part, to the shadow casted over this work by the anonymous treatise On Sublimity which was attributed to Cassius Longinus for a long time; in part, to the fact that this treatise and the rest of Cassius Longinus’ work is preserved in fragments; in part, because his most famous disciple, Porphyry, left his tutelage to follow the teachings of the most reputed Plotinus, who considered Cassius Longinus a philologist, but not a philosopher. Regardless of the reasons that contributed to eclipse the work of Cassius Longinus, namely, the unphilosophical spirit Plotinus saw in him or the poor quality of the sources we have for his study; the work of this author carries valuable information for the reconstruction of intellectual activity of the time. My aim is to examine one of the cases where Cassius Longinus can be an exceptional witness of the scholarly and philosophical activity which constitutes the Platonic tradition in Late Antiquity. At the end of the Ars Rhetorica’s chapter devoted to utterance (Ï€ÎµÏá½¶ Î»ÎÎ¾ÎµÏ‰Ï‚) Cassius Longinus exposes his theory of rhetoric period. The fragments of the commentary that Cassius Longinus made on Plato’s Timaeus preserved in the commentary of Proclus sheds light on how Cassius Longinus received Plato's dialogue and applied his exegetical work from a stylistic point of view (in accordance with his work in rhetoric), but also from a philological one. I want to explore, to the extent that the fragmentary material allows me, the link between logic and aesthetics emphasized in the Ars Rhetorica in the light of Cassius Longinus’ own exegetical work on Plato. Thus, it may be possible to reconcile the philological and philosophical work of our author while shedding light on one of the chapters of the Platonic tradition in Late Antiquity.